MARKETING STRATEGY OF PRODUCTION “KELADI” CHIPS IN BIAUNG VILLAGE, PENEBEL, TABANAN DISTRICT - Sumardani, Ni Luh Gde (Buletin Udayana Mengabdi, 2020)
Business opportunity is an important key in the marketing process because marketing will run smoothly if you get the desired business opportunity. The marketing system will be able to analyze the advantages and disadvantages of competitors, as well as the extent to which the ability to compete with them in all aspects, be it in terms of price, service and quality provided to consumers. Taro (Colocasia sp.), In Bali called keladi, is a food plant from tuber crops, including the taro tribe (Araceae) which is known as people's food and usually this taro when harvested is processed into several snacks. Processed “keladi” chips have a good business opportunity if managed properly, paying attention to processing, packaging, marketing, quality and quantity as well as health protocols, both in the production and marketing of these products. The results of financial analysis related to the production of “keladi” chips in Biaung Village, from 20 kg of “keladi” (IDR 7,000,00/kg) to 70 packs of “keladi” chips with a selling price of IDR. 8,000,00/packs with the new packaging; the gross income is Rp. 560,000, - and with a production cost of IDR. 330,000,00; net income of IDR. 230,000,00; with an R / C ratio of 1.7. The conclusion is that the “keladi”chips business that has been packaged in special packaging, the production of the community in Biaung Village, Penebel District, Tabanan Regency, is very feasible to be developed.